IDENTIFIKASI JAMU YANG BEREDAR DI KOTA KENDARI MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-VIS - Muhamad Handoyo Sahumena; Ruslin Ruslin; Asriyanti Asriyanti; Endah Nurrohwinta Djuwarno (State University of Gorontalo, 2020)
Jamu is a traditional medicine that contains ingredients or ingredients derived from plants, animals, minerals, or mixtures of these ingredients that have been hereditary for medicinal use. However, some industry players add Medicinal Chemicals (BKO) such as mefenamic acid into herbal medicine. This study aims to determine the validity of the method in the analysis of mefenamic acid by UV-Vis spectrophotometry on herbs circulating in several markets in Kendari City. The sampling technique used in this study is purposive sampling method so that it gets 5 herbal samples. The study began with method validation to ensure the accuracy of the method in determining the level of mefenamic acid in the sample. The results of the method validation show that this method is good for detecting the presence of mefenamic acid BKO in herbal medicine with a validation parameter value that is the correlation value (r) of 0.998; detection limit (LOD) 0.48 µg / mL; limit of quantification (LOQ) 1.63 µg / mL; intraday and interday precision expressed with the value of relative standard deviation% respectively 0.014% and 0.013%; and the accuracy stated in% recovery is 95.41% (80%), 99.04% (100%), and 102.5% (120%). The results of the analysis of the sample using a validated method showed that there were herbs with mefenamic acid BKO content of 0.8%.